2019
DOI: 10.34739/zn.2019.47.05
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Performance of an Economy

Abstract: The success of a national economy and the economic development of a country are mainly assessed based on economic indicators. The Gross Domestic Product (GDP) is the most commonly used indicator at national and regional levels. The informational power of GDP is limited, so alternative ways of measuring economic development and well-being have begun to be used, of which the Human Development Index (HDI) is the best known and the most accessible. The aim of this research is to highlight the areas that are to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Apart from other things, it was pointed out that the differences between EU regions, regarding economy, demand running an ad hoc policy. In turn, in the research reported in the work by Jílková and Skaličková (2019), the main goal is to indicate areas which should be taken into account while assessing economic development and affluence, in particularsocial and environmental factors. The authors also pointed to methods of measuring econmic development, which are an alternative in relation to the most frequently used economic indexes that measure economic development.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from other things, it was pointed out that the differences between EU regions, regarding economy, demand running an ad hoc policy. In turn, in the research reported in the work by Jílková and Skaličková (2019), the main goal is to indicate areas which should be taken into account while assessing economic development and affluence, in particularsocial and environmental factors. The authors also pointed to methods of measuring econmic development, which are an alternative in relation to the most frequently used economic indexes that measure economic development.…”
Section: Introductionmentioning
confidence: 99%